(untitled) (Новітні інформаційні системи та технології, 2016)
Network simulation is the most useful and common methodology used to evaluate different network topologies without real world implementation. The main focus of this paper is to compare the characteristics, open source network simulators based on the following parameters: CPU utilization, memory usage, computational time, and scalability.